Physical-chemical properties of sodic alkaline soil in micro scale and its influence on water and salinity transportation - LUO Jin-ming; DENG Wei; ZHANG Xiao-ping; LI Xiu-jun; YANG Fan (浙江大学学报. 农业与生命科学版, 2008)
Based on in-situ observation and analysis in laboratory, soil physical-chemical properties, water and salinity transportation feature in micro scale (a 32-m-long transect) were discussed. Results show that soil distribution pattern in saline soil area was sodic saline meadow soil-shallow columnar sodic alkaline soil-white crust sodic alkaline soil-mid columnar sodic alkaline soil. Sodic alkaline soil lay in micro slope or in micro high plain, and texture of which was silty sub slay-slay-silt-gravel; saline meadow soil lay in the relative low basin, and the main component of which was silt and gravel. Soil physical-chemical properties and micro relief influenced water transportation between soil profile and shallow groundwater. Fluctuation of groundwater was pretty correlated with precipitation transportation in saline meadow soil profile. Shallow basin (sodic saline meadow soil) became run-off sink. Frozen-thawing action was an important factor for soil salinity accumulation in Songnen plain. The frozen layer of sodic saline meadow soil became shallow aquifer sink in frozen period. A great deal of aquifer water transported and stored (soil water content was up to 50%) in frozen layer of saline meadow soil. And that might be an important reason for the shallow groundwater level abruptly descending during frozen season. Under the influence of freezing action, salinity transported from sub-layer to frozen layer of alkaline soil in surface and accumulated there. In thawing season, accumulation of salinity in surface aggravated saline degree.